Mental health: "it is a subject where most pharmacists [or pharmacy] students have no more knowledge than the general public" - H. C. Gorton; J. Strawbridge; H. Macfarlane (Taylor & Francis Group, 2023)
Abstract Background Mental health is a global health priority, and pharmacists have a valuable role in improving outcomes in all sectors of practice. This study sought to explore pharmacy students' views on teaching and learning of mental health and future practice. Methods An anonymous online questionnaire was distributed to pharmacy students in the UK and Ireland in February 2020 via the Qualtrics™ platform and 232 students responded. The questionnaire was originally intended to explore the provision of Mental Health First Aid (MHFA) teaching and the quantitative analysis has been previously reported. Students were invited to comment on their views about MHFA. The open-ended question: 'Do you have any other comments about mental health teaching and learning in the MPharm degree?' was also included. The rich free-text data were analysed, and themes identified. Results Three major themes were identified: (i) Mental Health is important; (ii) Pharmacist roles and (iii) So, Teach me. A fourth theme, Stigma, crosscut all the themes. Conclusions Pharmacy students appreciate the importance of mental health care. The majority recognise the role of the pharmacist in providing person-centred care and the potential to enhance this role. Students are keen to learn more, and acquire the confidence and skills to contribute in the future. They would like an integrated approach and have more opportunities to learn from patients. Addressing stigma is an important consideration for educators.